Advanced structural characterisation of agar-based hydrogels: Rheological and small angle scattering studies. (15th May 2020) - Martínez-Sanz, Marta; Ström, Anna; Lopez-Sanchez, Patricia; Knutsen, Svein Halvor; Ballance, Simon; Zobel, Hanne Kristine; Sokolova, Anna; Gilbert, Elliot Paul; López-Rubio, Amparo
Graphical abstract: Highlights: Alkali pre-treatment increases agar purity but reduces its molecular weight. Sonication reduces the agar content and the molecular weight. Gelation occurs by formation of agarose double helices and association into bundles. Gelation mechanism is not affected by the presence of non-agar components. Mechanical properties of the hydrogels can be adjusted by the extraction protocol. Abstract: Agar-based extracts from Gelidium sesquipedale were generated by heat and combined heat-sonication, with and without the application of alkali pre-treatment. Pre-treatment yielded extracts with greater agar contents; however, it produced partial degradation of the agar, reducing its molecular weight. Sonication produced extracts with lower agar contents and decreased molecular weights. A gelation mechanism is proposed based on the rheological and small angle scattering characterization of the extracts. The formation of strong hydrogels upon cooling was caused by the association of agarose chains into double helices and bundles, the sizes of which depended on the agar purity and molecular weight. These different arrangements at the molecular scale consequently affected the mechanical performance of the obtained hydrogels. Heating of the hydrogels produced a gradual disruption of the bundles; weaker or smaller bundles were formed upon subsequent cooling, suggesting that the process was not completely reversible.